Effects of Excess Cu Addition on Photochromic Properties of AgCl-Urethane Resin Composite Films - Hidetoshi Miyazaki; Hirochi Shimoguchi; Hiroki Nakayama; Hisao Suzuki; Toshitaka Ota (Advances in Materials Science and Engineering)
AgCl-resin photochromic composite films were prepared using AgNO3, HCl-EtOH, CuCl2 ethanol solutions, and a urethane resin as starting materials. The AgCl particle size in the composite films, which was confirmed via TEM observations, was 23–43 nm. The AgCl composite films showed photochromic properties: coloring induced by UV-vis irradiation and bleaching induced by cessation of UV-vis irradiation. The coloring and bleaching speed of the composite film increases with increasing CuCl2 mixing ratio.